PERBANDINGAN PERAN SUMBER PERMODALAN SEBAGAI PENGUATAN USAHA MIKRO KECIL MENENGAH (UMKM) SEBELUM DAN SELAMA COVID-19 (2018 S.D 2021) - Anggi Prastyono; Nasutra (Journal Publicuho, 2024)
The Micro, Small, and Medium Enterprises (MSMEs) have become one of Indonesia's economic sectors affected by Covid-19. The capital sources for MSMEs before and during COVID-19 (2018 to 2021) have presented two distinct situations, which we address in this study. The research aims to analyze the differing situations regarding the primary capital sources for MSMEs before and during COVID-19 (2018 to 2021). The research methodology involves a qualitative literature review utilizing data from articles on Google Scholar between 2018 and 2021 using the keyword "MSME capital sources," totalling 50 articles before and during COVID-19. The findings reveal that MSMEs, in the two situations, have distinct focuses on capital sources. Before COVID-19, MSMEs primarily relied on Banking Institutions for capital, while during COVID-19, they shifted focus towards non-banking institutions such as Fintech, Baitul Maalwat Tamwil, Venture Capital, Government, Personal Funds, Pawnshops, Credit Institutions, Cooperatives, State-Owned Enterprises (BUMN), and Village-Owned Enterprises (BUMDes). Furthermore, the role of funding from both banking and non-banking sources is crucial in supporting the sustainability of MSMEs.